Detecting clinical progression from abnormal regional brain volumes at baseline in genetic frontotemporal dementia: A GENFI study. (31st December 2021) - Bocchetta, Martina; Todd, Emily G; Nicholas, Jennifer M; Peakman, Georgia; Cash, David M; Convery, Rhian S; Russell, Lucy L; Thomas, David L; Iglesias, Juan Eugenio; van Swieten, John C; Jiskoot, Lize C.; Seelaar, Harro; et al.
Abstract: Background: Genetic frontotemporal dementia is highly heterogeneous, with different progression patterns seen between individuals. Using in vivo MR images from the Genetic FTD Initiative (GENFI), we aimed to identify clinical progression in genetic mutation carriers from their brain volumes at baseline. Method: Cortical and subcortical volumes of interest (VOIs) were generated using automated parcellation methods on volumetric 3T T1‐weighted MRI scans for 480 carriers (198 GRN, 202 C9orf72, 80 MAPT ). W‐scores for 79 VOIs were computed from a linear regression model carried out on 298 non‐carrier cognitively normal controls adjusting for the effect of age, sex, total intracranial volume and scanner type. Carriers were divided into three disease stages based on their global CDR® plus NACC FTLD score (CDR‐GS): asymptomatic (0), possibly or mildly symptomatic (0.5) and fully symptomatic (1 or more). Cut‐off points for each VOI were derived from Youden indices estimated with ROC curves to distinguish between CDR‐GS=0 and CDR‐GS≥1 within each gene. CDR‐GS=0.5 carriers (30 GRN, 32 C9orf72, 13 MAPT ) were classified as 'normal' or 'abnormal' based on these cut‐off points. We compared the CDR® plus NACC FTLD sum‐of‐boxes scores (CDR‐SOB) at one year follow‐up in these two groups. Result: Compared to those with normal baseline volumes, C9orf72 expansion carriers at CDR‐GS=0.5 showed significantly higher CDR‐SOB scores at follow‐up if they had abnormal volumes in the total frontal (+5 points), orbitofrontal (+3), dorsolateral prefrontal (+6), or anterior cingulate (+4) cortices, the basal‐paralaminar amygdala region (+2), CA1 region of the hippocampus (+4), total hippocampus (+6), cerebellar lobule VIIIb (+4), or lateral ventricles (+8). GRN mutation carriers showed significantly higher CDR‐SOB scores if their volumes were abnormal in the frontal (+10), parietal (+14), insula (+8), orbitofrontal (+12), or medial parietal (+7) cortices, or the total hippocampus (+10). MAPT mutation carriers with abnormal volumes in the lobule VI and dentate nucleus had 1 point higher CDR‐SOB scores at follow‐up. Conclusion: Abnormal baseline volumes in specific VOI within each of the genetic groups were related to worse CDR‐SOB scores over time. Future studies including longer follow‐up intervals and other longitudinal biomarkers are needed to explore this further.